2012
DOI: 10.9790/5736-0153138
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Use of Performance Enhancing Drugs Among Nigeria Elite Athletes

Abstract: The use of drugs to enhance sports performance by athletes is currently a world wide social problem. Although, sports administrators are doing a lot to discourage the practice, yet the incidence appears to be on the increase. It is against this background that the study investigated the knowledge and use of performance enhancing drugs among Nigerian elite athletes. Also, it examined the influence of chronological age of a selected sample of elite athletes and type of sports they engage in on the use of perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This showed that the national athletes are using alcohol, drug, excessive drinking of coffee, smoking and showing aggressive behavior to cope with their stress. This result supported by the research done by [20] and [21], that elite athletes uses more drugs compared with lower skilled athletes. Research indicates that the usage of alcohol and smoking is higher in athletes compared to non-athletes [22,13,23].…”
Section: *P=05supporting
confidence: 75%
“…This showed that the national athletes are using alcohol, drug, excessive drinking of coffee, smoking and showing aggressive behavior to cope with their stress. This result supported by the research done by [20] and [21], that elite athletes uses more drugs compared with lower skilled athletes. Research indicates that the usage of alcohol and smoking is higher in athletes compared to non-athletes [22,13,23].…”
Section: *P=05supporting
confidence: 75%
“…Performance-enhancing drugs considered as a wide variety of drugs intended for the aim of promoting the activity, increasing the endurance and alertness, strengthening the muscular power of the users and to perform beyond ability. Many users tend to use them in the hope of correcting their body dissatisfaction and social recognition [3 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the number of causes, it has been acknowledged that the athletes use a variety of drugs engaging in sports [13]. Numerous performance improving ingredients and processes provide a chance in sport improvement to athletes for several years [14]. Student-athletes mostly reproduce the drug usage practices from their nonathletic peers that may be interested to consume the ergogenic ingredients to develop their sport performance [13].…”
Section: Introductionmentioning
confidence: 99%
“…As the outcome of the features and biological influences of drugs, they inoculate extensive support to athletes in their performance [14]. In modern years, there have been lots of mature athletes involved in taking shameful performance improving ingredients [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation